Phosphatases of Regenerating Liver (PRL) as Therapeutic Targets in Cancer - Wang, Wenxuan (McGill Science Undergraduate Research Journal, 2018)
Background: Phosphatases of regenerating liver (PRL) represent a class of protein tyrosine phosphatases with oncogenic activity. PRL overexpression enhances cell proliferation, transformation, and promotes metastasis in many human cancers. Most notably, PRLs interact with a family of magnesium transporters, cyclin M (CNNM), to regulate intracellular Mg2+ levels. Thus, PRLs are attractive therapeutic targets given their role in oncogenic and tumour suppressor signaling pathways by modulating cellular growth. Methods: Academic research articles were obtained by searching key terms in the PubMed database. This review specifically focuses on the articles that provided a comprehensive overview of PRLs, CNNMs, and small molecule inhibitors of PRLs. Summary: This review discusses the role of PRLs in promoting cancer metastasis and explores current strategies for targeting PRL activity through the use of small molecule inhibitors. Although several potent PRL inhibitors have been discovered, improvements must be made prior to clinical applications. Therefore, understanding the molecular basis of PRL inhibition is essential for developing novel therapeutic agents in cancer treatments.